(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current state of psychological disorders in health students at Dai Nam University in 2022 and some related factors. Research method: Cross-sectional descriptive study conducted on 412 health students at Dai Nam University in 2022. Psychological disorders were measured using the PQH9 scale. Results: The rate of students with psychological disorders in the study was 54.4%. The rates of "feeling bad about yourself - or feeling worthless or have disappointed yourself or your family" and "Loss of appetite or overeating" everyday account for 11.1% and 10.6%. The rate of psychological disorders is highest among single students without a partner (56.5%) and lowest among married students (12.5%). Medical students have the highest rate of psychological disorders, accounting for 61.7%, and nursing students have the lowest rate, with 46.7%. Students with cell phone abuse and sleep disorders had significantly higher rates of psychological disorders. The above differences are statistically significant with p < 0.05. Conclusion: The rate of psychological disorders in Health Science students is relatively high. Psychological disorders are related to relationship status, field of study, sleep disorders and smartphone abuse. Therefore, there is a need for psychological support measures in health science students.